2017
DOI: 10.1186/s12957-017-1228-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of colon cancer initially presenting as colon perforation and obstruction

Abstract: BackgroundEmergency complications of colon cancer include perforation and obstruction which were recognized as poor prognostic factors. Few studies have directly compared the outcomes of these two groups. In this study, we evaluated mortality and morbidity in patients with colon cancer initially presenting as perforation and obstruction.MethodsNewly diagnosed colon cancer cases initially presenting with perforation or obstruction at Tzu Chi General Hospital, Hualien, Taiwan, between 2009 and 2015 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 20 publications
1
43
1
8
Order By: Relevance
“…According to other studies [36,37], our patients whose tumor occurred with obstruction or perforation showed a worse DFS compared with the other tumor manifestations, although with a trend towards significance (HR = 2.65, 95% CI 1.00-7.01, p = 0.050).…”
Section: Discussionsupporting
confidence: 56%
“…According to other studies [36,37], our patients whose tumor occurred with obstruction or perforation showed a worse DFS compared with the other tumor manifestations, although with a trend towards significance (HR = 2.65, 95% CI 1.00-7.01, p = 0.050).…”
Section: Discussionsupporting
confidence: 56%
“…The prevalence of perforation in colon cancer patients is reported to be 3–10% [ 1 – 3 ]. More specifically, colon cancer patients with perforation exhibit a greater frequency of recurrence and poorer overall survival (OS) compared with those without perforation [ 4 , 5 ]. In the National Comprehensive Cancer Network guidelines, colon cancer with perforation is categorized a high-risk feature [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if a SEMS or TDT is not technically feasible, a decompressing stoma may be necessary to achieve a symptom-free condition for the patient. Although the mortality rate of these patients in the short term is high, little is known about the long-term outcomes of recurrence and prognosis [6,7]. In the present study, we analyzed the specific prognosis (except for short-term mortality such as progression of disease and postoperative complications) in colon cancer patients with and without an MLBO.…”
mentioning
confidence: 99%